Manajemen Risiko Kredit pada Pembiayaan UMKM Berbasis Jaminan BPKB Motor: Evaluasi Sistem Verifikasi dan Survei - Farkha Fitriyani; Prayitno Prayitno (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study examines the document verification process and field survey implementation in motorcycle BPKB-backed financing for the MSME sector and their impact on non-performing loan (NPL) risk. The research addresses the high risk of problematic financing due to weaknesses in identity validation, collateral survey accuracy, and income verification during the initial screening. A qualitative approach with a case study design was used, including data from 250 debtors and interviews with Credit Marketing Officers (CMOs) and credit analysts. Data analysis involved data reduction, display, and thematic conclusion drawing, supported by descriptive quantitative analysis. The findings show an NPL rate of 28%, with 75% of debtors with identity discrepancies defaulting, 63% of those with insufficient surveys facing delinquency, and 64% of those with unverified income failing to meet obligations. These results highlight the link between administrative verification quality, field survey procedures, and default risk. The study suggests enhancing digital-based identity validation systems, standardizing survey procedures, and improving income verification methods tailored to MSME characteristics as strategic measures to mitigate risk. The findings offer practical insights for financing company management in strengthening internal controls and contribute to the development of credit risk management literature in non-bank MSME financing.